4 x tiles and 3 negative tiles = 5 x tiles and 4 positive tiles.

Examine the algebra tiles.

Which equation is being modeled?

4x + 3 = 4x + 5
–3x + (–3) = 4x + 5
4x + (–3) = 5x + 4
–3x + 4 = 5x + 4

1 answer

To analyze the situation represented by the algebra tiles:

The statement "4 x tiles and 3 negative tiles = 5 x tiles and 4 positive tiles" can be translated into an algebraic equation.

Let's break it down:

  • "4 x tiles" can be represented as \(4x\).
  • "3 negative tiles" can be represented as \(-3\).
  • "5 x tiles" can be represented as \(5x\).
  • "4 positive tiles" can be represented as \(+4\).

Putting it all together, we have:

\[ 4x - 3 = 5x + 4. \]

Now, let's rewrite it for clarity:

This can be rearranged to see if it matches any of the provided options:

  • Bring all terms involving \(x\) on one side: \[-3 = 5x - 4x + 4,\] simplifying gives: \[-3 = x + 4.\]

So we can match the original equation with the options.

The closest option from what you provided is:

4x + (–3) = 5x + 4.

Thus, the equation being modeled is:

4x + (–3) = 5x + 4.